Combined effect of recombinant CD19xCD16 diabody and thalidomide in a preclinical model of human B cell lymphoma - Schlenzka, Jana; Möhler, Thomas; Kipriyanov, Sergey M.; Kornacker, Martin; Benner, Axel; Bähre, Alexandra; Stassar, Marike J. J. G.; Schäfer, Holger; Little, Melvyn; Goldschmidt, Hartmut; Cochlovius, Björn (Anti-cancer drugs, 2004)
Combining different treatment strategies offers the possibility of improving treatment results for cancer patients. The aim of our study was therefore to investigate the combination of treatment of established s.c. human B non-Hodgkin's lymphoma in severe immune deficient mice using a recombinant bispecific CD19×CD16 diabody (targeting natural killer cells to CD19+ cells) and the angiogenesis inhibitor thalidomide. Monotherapy with either thalidomide or diabody caused an approximate 50% reduction in tumor growth rate. The combined treatment showed evidence for a synergistic effect resulting in a 74% reduction in median tumor size. In the combined treatment group, two of five animals had complete remissions of their s.c. tumor. These results suggest that a combination treatment with recombinant diabodies and angiogenesis inhibition represents a useful approach in cancer therapy.